Etiquette Behavior in the Context of University Organizational Culture - O. I. Danilenko; M. A. Perminova (Высшее образование в России)
The aim of this study is to reveal interrelationship between the notions of etiquette behavior of students and teachers and the characteristics of organizational culture at universities. Methods. The research is based on a survey. The sample included 141 students and 69 teachers from Russian universities. A set of diagnostic methods was used to gather the empirical data. Data on teachers’ and students’ attitude to institutionalization of etiquette rules and dress code as well as students’ compliance with etiquette rules were collected using the author’s questionnaire; data on evaluation of etiquette functions were obtained through the questionnaire Subjective Evaluation of Etiquette Functions’ Significance by O.I. Danilenko, data on existing and preferred organizational culture in the respondents’ universities – through Organizational Culture Assessment Instrument (OCAI) by K. Cameron and R. Quinn. Results. Correlations between indicators, characterizing etiquette behavior and current organizational culture type, were identified in both groups: positive for clan and adhocracy culture type, negative – for hierarchical. Statistically significant positive correlations between evaluation of etiquette functions' significance and evaluation of students’ compliance with etiquette rules and clan culture, negative correlations between the same indicators of etiquette behavior and hierarchical culture were revealed in the students’ group. In teachers’ group, evaluation of etiquette functions' significance, positive attitude to institutionalization of etiquette rules and dress code are correlated positively with clan and adhocracy organizational culture, negatively – with hierarchical. Conclusion. The gathered data indicate: the higher both students and teachers evaluate characteristics of clan and adhocracy culture, the higher is their evaluation of the importance of etiquette behavior. The higher are values of hierarchical culture characteristics, the lower is evaluation of etiquette importance.